Treatment of the Induration of the Soft Tissue of the Lower Eyelids After Accidental Oil Injections - Vladimir Safronov, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Injection cosmetic procedures have shown rapid continuing growth in the last 2 decades. Various substances are injected into the periorbital region for skin quality increase and correction of tear trough deformity, including hyaluronic acid, peptides, collagen, and others. Sometimes patients get accidentally injected with different substances that are not approved for cosmetic treatment in this anatomic area. The author presents a case of a 51-year-old woman, injected with unknown oil solution into the lower eyelid skin by the local dermatologist. Inflammation and induration of the skin of the lower periorbital region have occurred after these injections. The patient was treated conservatively until the acute process stopped, and then surgical correction was performed to correct skin and orbicularis oculi muscle induration changes. Surgical treatment included direct oil cyst excision and removal after injection changed tissues between skin and orbicularis oculi muscle. The patient was observed for scheduled appointments and conservative treatment to prevent unfavorable scar formation and lower eyelid deformity. Although different kinds of oil substances are not approved for skin injections for cosmetic purposes, accidental injections occur and may lead to terrible results. Methods to correct eyelid deformity after oil solution injections are not presented in the literature. In this article, the author presents a case report with the method of correction of induration of soft tissues of the lower eyelids occurring after oil injections. Although cases like this are rare, they require correct surgical solution to provide a good aesthetic result after the treatment.